1999
DOI: 10.1097/00007890-199909270-00021
|View full text |Cite
|
Sign up to set email alerts
|

The Control of Epidermal Stem Cells (Holoclones) in the Treatment of Massive Full-Thickness Burns With Autologous Keratinocytes Cultured on Fibrin1

Abstract: Our data demonstrate that: (i) cultured autografts bearing stem cells can indeed rapidly and permanently cover a large body surface; and (ii) fibrin is a suitable substrate for keratinocyte cultivation and transplantation. These data lend strength to the concept that the success of cell therapy at a clinical level requires cultivation and transplantation of stem cells. We therefore suggest that the proposal of a culture system aimed at the replacement of any severely damaged self-renewing tissue should be prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
270
0
11

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 337 publications
(289 citation statements)
references
References 52 publications
8
270
0
11
Order By: Relevance
“…Informed consent was obtained from the parents. Keratinocytes were cultivated on a feeder layer of lethally irradiated 3T3-J2 cells as described (28,30,33) and passaged at the stage of subconfluence.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Informed consent was obtained from the parents. Keratinocytes were cultivated on a feeder layer of lethally irradiated 3T3-J2 cells as described (28,30,33) and passaged at the stage of subconfluence.…”
Section: Methodsmentioning
confidence: 99%
“…Keratinocytes can generate cohesive sheets of stratified epithelium that maintains virtually the same differentiation features and gene expression pattern of its in vivo counterpart so that it can be routinely transplanted in patients suffering from large skin or mucosal defects (31)(32)(33). When primary keratinocytes are seeded onto dead de-epidermized dermis in organotypic cultures (29), mature HDs are formed in vitro (30).…”
mentioning
confidence: 99%
“…Several studies have shown that progenitor epidermal cells are better than differentiated ones in the generation of successful tissue-engineered skin [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The use of fibrin sealant improves the percentage of skin graft take, and evidence also suggests improved hemostasis and a protective effect resulting in reduced bacterial infection 17 . Cell culture studies have shown that the relative percentage of holoclones, meroclones and paraclones of basal keratinocytes is maintained when keratinocytes are cultivated on fibrin, proving that fibrin does not induce clonal conversion and consequent loss of epidermal stem cells 18 . When they are applied on massive full-thickness burns, the take of keratinocytes is high, reproducible, and permanent 14 .…”
Section: Discussionmentioning
confidence: 99%
“…When they are applied on massive full-thickness burns, the take of keratinocytes is high, reproducible, and permanent 14 . Furthermore, it allows a significant reduction of the costs of cultured autografts and eliminates problems related to handling and transportation 14,18 . However, to obtain these results, it has been emphasized that the presence of a "feeder layer" of lethally irradiated mouse fibroblasts is an absolute requirement 14 ; and because fibrinolysis occurs rapidly as soon as epidermal cells or irradiated 3T3 cells are added 13 , until now there are no long-term evaluations of the in vitro differentiation process in the epidermis reconstituted under this condition.…”
Section: Discussionmentioning
confidence: 99%